2022
DOI: 10.1177/00369330221134233
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder recurrences following ureteroscopic biopsies of upper tract urothelial cancers: a multi-centre observational study with genomic assessment for clonality

Abstract: Background and aims Urinary bladder recurrences (UBRs) after radical nephroureterectomy (RNUx) are a known challenge in patients with upper-tract urothelial cancers (UTUCs). We aim to assess factors associated with UBR and clonal-relatedness with resected UTUC. Methods Patients who underwent RNUx for UTUC between 1998 and 2015 in five institutions were identified. Clonal relatedness between primary UTUC and subsequent UBR in a sub-cohort was assessed using next-generation sequencing. A Kaplan–Meier curve was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The extent to which such tumors are clonally related to UTUC has varied in previous studies. [9][10][11][12] The pattern here may suggest that, particularly, later-forming tumors could be the result of a new, in situ oncogenic process; notwithstanding, such temporal relationships remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 85%
“…The extent to which such tumors are clonally related to UTUC has varied in previous studies. [9][10][11][12] The pattern here may suggest that, particularly, later-forming tumors could be the result of a new, in situ oncogenic process; notwithstanding, such temporal relationships remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 85%
“…Although diagnostic URS biopsy is an important component in the diagnosis of UTUC, allowing for patient risk stratification, it can present a technical challenge. As invasive preoperative diagnostic modalities are associated with the risk of urinary bladder recurrence (UBR), URS biopsy is a significant risk factor for UBR in UTUC ( 16 ). Thus, we instead used a flexible ureteroscope to probe the renal pelvis and ureter of the hypothermic isolated kidney to further clarify the presence of tumour metastasis and implantation, which was a feasible approach.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic URS without biopsy was not associated with worse IVRFS [7]. Table 1 summarizes the studies assessing the association between URS, IVR (intravesical recurrence), and RFS (recurrence-free survival) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A study on 143 patients demonstrated a pathological phenotype-specific association between pre-operation URS and oncological outcomes, as the subgroup of patients with non-papillary and ≥pT3 UTUC had poorer overall and progression-free survival [23].…”
Section: Ureterorenoscopy and Biopsymentioning
confidence: 99%